PENGARUH ELECTRONIC WORD OF MOUTH DAN REPUTASI PENJUAL TERHADAP KEPUTUSAN PEMBELIAN GENERASI Z DENGAN KEPERCAYAAN KONSUMEN SEBAGAI MEDIASI - Prisca Restu Triana; Muchammad Agung Miftahuddin; Tri Septin Muji Rahayu; Meydy Fauziridwan (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The increasing use of online shopping platforms among young consumers has elevated the importance of understanding the determinants of purchasing decisions. In this context, Electronic Word of Mouth (e-WOM) and seller reputation serve as essential sources of information that help shape consumer evaluations before making a purchase. This research aims to analyze the influence of these two factors on purchasing decisions and to examine the mediating role of consumer trust among Shopee users in Purwokerto.Methods: This quantitative study involved 120 Shopee users in Purwokerto who completed an online structured survey. The study applied PLS-SEM as an analytical approach to assess direct causal effects and mediation pathways among the research variables.Results: The analysis indicates that both e-WOM and seller reputation significantly impact consumer trust and purchasing decisions. Furthermore, consumer trust was identified as a partial mediator in the relationships between e-WOM and seller reputation on purchasing decisions. These results suggest that the quality of information and sellers’ images on online platforms play a crucial role in enhancing consumer confidence before completing a transaction. Keywords: Customer Trust, Electronic word of mouth, Purchase Decisions. Seller Reputation.